2021
DOI: 10.1111/jpm.12759
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Korean 12‐item Perception of Aggression Scale

Abstract: What is known on the subject?• The importance of and interest in nurses' attitudes towards and subjective experience with workplace violence in clinical settings is increasing.• The prevalence of patient-perpetrated violence against Korean nurses in hospital settings is highly prevalent.• Only few instruments are available to measure the nurses' perception of patient aggression in Korea. What the paper adds to existing knowledge?• This is the first study to assess the linguistic and psychometric reliability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
(43 reference statements)
2
2
2
Order By: Relevance
“…First, our findings showed that the coping styles of South Korean nurses may be related to underestimating or not recognizing the problem of violence. This result supports previous studies showing that nurses with a greater perception of coping with workplace violence were found to be more successful in their struggle with violence [ 12 , 13 , 28 , 37 , 62 , 63 ]. Therefore, workplace violence training programs for identifying the patterns of the workplace violence process can help to improve nurses’ coping styles [ 12 , 13 , 28 , 37 , 62 , 63 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…First, our findings showed that the coping styles of South Korean nurses may be related to underestimating or not recognizing the problem of violence. This result supports previous studies showing that nurses with a greater perception of coping with workplace violence were found to be more successful in their struggle with violence [ 12 , 13 , 28 , 37 , 62 , 63 ]. Therefore, workplace violence training programs for identifying the patterns of the workplace violence process can help to improve nurses’ coping styles [ 12 , 13 , 28 , 37 , 62 , 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…A higher score indicates a more positive appraisal for aggression by a patient (range 12–60). Cronbach’s α coefficients for the dysfunctional/undesirable phenomenon, functional/comprehensible phenomenon, and protective measure were between .76 and .83 in Wong and Chien [ 40 ] and .76 and .92 in Nam et al [ 37 ], whereas they were .84 and .90 in our study.…”
Section: Methodscontrasting
confidence: 59%
See 1 more Smart Citation
“…A higher score indicates a more positive appraisal for aggression by a patient (range 12-60). Cronbach's α coe cients for the dysfunctional/undesirable phenomenon, functional/comprehensible phenomenon and the protective measure were between .76 and .83 in Wong and Chien [25] and .76 and .92 in Nam et al [22], while they were .84 and .90 in our study.…”
Section: Perception Of Aggression Scale (Poas)contrasting
confidence: 50%
“…Nurses' attitudes of aggression were measured using the Perception of Aggression Scale (POAS) [22,23]. The POAS consists of 12 items and comprises three subscales (i.e., dysfunctional/undesirable phenomenon, functional/comprehensible phenomenon, and protective measure) [22][23][24][25]. Each item was measured on a ve-point Likert scale (1 = "strongly disagree" and 5 = "strongly agree").…”
Section: Perception Of Aggression Scale (Poas)mentioning
confidence: 99%